Performance of Nano-Electromechanical Systems as Nanoparticle Position Sensors - Orhan, Ezgi; Yuksel, Mert; Ari, Atakan B.; Yanik, Cenk; Hatipoglu, Utku; Yağci, Ahmet Murat; Hanay, M. Selim (Frontiers in Mechanical Engineering, 2020)
Nanoelectromechanical systems (NEMS) have been utilized as sensitive mass sensors in many applications such as single cell characterization, volatile organic biomarker detection and single molecule mass spectrometry. Using the frequency shift detection, mass of single analytes can be resolved. Mass detection sensitivity can be further improved by accurate measurement of the position, unlocking extra capabilities in nanoscale positioning and manipulation applications. Here, we studied the position sensing performance of two-mode NEMS resonators during detection of single 20 nm gold nanoparticles (GNPs). By recording the position of each particle with frequency shift sensing, the position detection accuracy was evaluated for different beam models and the results are validated by SEM imaging Our results indicate that the position sensing accuracy, and therefore the mass sensing accuracy, of nanomechanical resonators depends critically on the use of appropriate beam models.